MORPHOLOGICAL STUDY ON VERBAL INFLECTIONAL AND DERIVATIONAL PROCESS IN SASAK LANGUAGE - Zaenul Fikri (LPPM Universitas Gunung Rinjani, 2019)
This study was meant to identify the affixes which occur thorough inflectional andderivational process in SLND and to identify the verbs which occur through zero derivation.This study deals with a qualitative research. The techniques were used to collect the datathrough observation, interview, and recording. The data were taken from native speaker ofNgeno – Ngene dialect in Apitaik village. The obtained data were then analyzed throughdistributional method and equal method. It showed that there are eleven types of affixesdealing with inflectional process of verbal construction, as follows: three types in terms ofprefixes (e.g. N-, ta-,be-), two types in terms of suffixes (e.g.-aŋ, -in), and six typesin terms of circumfixes (e.g. N-aŋ, ta - aŋ, N-in. ta-in, be-an, ke-an). In addition,There are seven types of affixes which occur through derivational process such as N-,be-, -aŋ, -in, ta-aŋ, ta-in and N-aŋ. Lastly, it is also found that there was achanging process of word class catergoy (e.g. Noun → Verb) without adding particularaffixes categorized as a zero derivation.